A Century Spent Combating Rabies in Morocco (1911–2015): How Much Longer? - Darkaoui, Sami; Cliquet, Florence; Wasniewski, Marine; Robardet, Emmanuelle; Aboulfidaa, Nadia; Bouslikhane, Mohammed; Fassi-Fihri, Ouafaa (Frontiers in Veterinary Science, 2017)
Rabies has no known beginning in Morocco and to date, government control efforts and plans fail to eradicate the disease. A review and analysis of available epidemiological data is crucial to learn lessons from the past and to propose effective actions. Legally, animal rabies is a notifiable disease since 1913 and legislation has been updated periodically since. Dogs has always been considered as both the disease’s vector and reservoir, while cattle, other herbivores and humans are victims. Animal rabies cases evolution from 1942 to 2015 is characterized by ascending phase then decreasing one following structured rabies control plan implementation in the 1980’s. Indeed, from 1986 to 2010, three rabies control plans have been conducted based on free of charge rabies vaccination of owned dogs through mass campaigns. The geographical distribution of rabies is stable over the years with highest cases number in rich rural areas and around cities. Human rabies cases are decreasing over the time (1976-2015) thanks to the opening of new antirabic treatment centers in the last decade which permit the administration of more PEP’s. After a century of rabies control, Morocco registered an average of 301 animal cases and 21 human cases annually for the last decade (2005-2015). Few reasons led to those limited results. The lack in law enforcement and moreover, the fact that the law don’t take into account responsible dog ownership aspect are of importance. Lack of dog population knowledge and management and intersectorial coordination deficiency are additional failure reasons. The gathered data will help to build a new strategy with a focus on a “One Health” approach. Dog population ecology parameters study is of primary importance. We estimated dog population to 2,8 million dogs based on human: dog ratio. Enhancing vaccination coverage of dog population is feasible by combining parenteral vaccination and complimentary oral vaccination. Updating legislation by inclusion of responsible dog ownership and law enforcement are crucial. Over the last century, Morocco registered a slow decreasing tendency in the number of animal and human rabies cases. Urgent strategy need to be implemented because rabies eradication is an achievable goal in Morocco.